2007
DOI: 10.1300/j013v46n01_03
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Shame: Self-Objectification and Young Women's Attitudes Toward Their Reproductive Functioning

Abstract: The purpose of this study was to measure and compare women's attitudes toward menstruation and breastfeeding and to determine whether self-objectification was associated with negative attitudes toward these events. We hypothesized that women who viewed menstruation as shameful would also report high levels of shame about breastfeeding and that women with greater self-objectification tendencies would have more negative or shameful attitudes toward both menstruation and breastfeeding. One hundred and seventy-six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(74 citation statements)
references
References 28 publications
1
65
0
2
Order By: Relevance
“…The following is a list (not exhaustive) of other consequences empirically associated with self-objectification: lower intrinsic motivation and self-efficacy (Gapinski, Brownell, & LaFrance, 2003); lower self-esteem (Choma et al, 2010); less life satisfaction (Mercurio & Landry, 2008); diminished cognitive performance Gay & Castano, 2010;Quinn, Kallen, Twenge, & Fredrickson, 2006); diminished physical performance (Fredrickson & Harrison, 2005); more negative attitudes toward breastfeeding (JohnstonRobeldo, Fricker, & Pasek, 2007) and reproductive functioning (Johnston-Robledo, Sheffield, Voigt, & Wilcox-Constantine, 2007;Roberts, 2004); greater fear and perceived risk of rape (Fairchild & Rudman, 2007); greater hostility toward other women (Loya, Cowan, & Walters, 2006); more self-injury (Muehlenkamp, Swanson, & Brausch, 2005); more substance abuse (Carr & Szymanski, 2011;Harell, Fredrickson, Pomerleau, & Nolen-Hoeksema, 2006); decreased use of sexual protection (Impett, Schooler, & Tolman, 2006); more dysfunctional exercise (Strelan, Mehaffey, & Tiggemann, 2003); and more support for cosmetic surgery (Calogero, Pina, Park, & Rahemtulla, 2010;Calogero, Pina, & Sutton, 2013).…”
Section: Consequences Of Self-objectificationmentioning
confidence: 99%
“…The following is a list (not exhaustive) of other consequences empirically associated with self-objectification: lower intrinsic motivation and self-efficacy (Gapinski, Brownell, & LaFrance, 2003); lower self-esteem (Choma et al, 2010); less life satisfaction (Mercurio & Landry, 2008); diminished cognitive performance Gay & Castano, 2010;Quinn, Kallen, Twenge, & Fredrickson, 2006); diminished physical performance (Fredrickson & Harrison, 2005); more negative attitudes toward breastfeeding (JohnstonRobeldo, Fricker, & Pasek, 2007) and reproductive functioning (Johnston-Robledo, Sheffield, Voigt, & Wilcox-Constantine, 2007;Roberts, 2004); greater fear and perceived risk of rape (Fairchild & Rudman, 2007); greater hostility toward other women (Loya, Cowan, & Walters, 2006); more self-injury (Muehlenkamp, Swanson, & Brausch, 2005); more substance abuse (Carr & Szymanski, 2011;Harell, Fredrickson, Pomerleau, & Nolen-Hoeksema, 2006); decreased use of sexual protection (Impett, Schooler, & Tolman, 2006); more dysfunctional exercise (Strelan, Mehaffey, & Tiggemann, 2003); and more support for cosmetic surgery (Calogero, Pina, Park, & Rahemtulla, 2010;Calogero, Pina, & Sutton, 2013).…”
Section: Consequences Of Self-objectificationmentioning
confidence: 99%
“…Further, higher scores on this subscale and the Self-objectification Scale (SOQ; were correlated with concerns about breastfeeding as embarrassing, particularly in front of others. In a study of undergraduate women's attitudes toward multiple reproductive events, Johnston-Robledo, Sheffield, Voigt, and Wilcox-Constantine (2006) found that young women with high scores on both the Self-surveillance and Body shame subscales of the OBCS also had high scores on measures of concern about breastfeeding as negatively impacting their bodies and as inappropriate in front of others.…”
Section: The Present Studymentioning
confidence: 99%
“…Healthcare providers and health educators should pay greater attention to socio-cultural aspects of menstruation, to address myths and unnecessary anxiety; to discuss women's concerns and fears; to support health care decisions based on more accurate information; and to help women to manage menstruation to fit with their lifestyles. This study reflected how menstruation and menstrual health continue to be shaped by shame, secrecy, and misperceptions (Johnston-Robledo et al, 2007). Researchers need to continue to explore the social, economic, and psychological aspects of problems related to menstruation, to understand how women construct and manage their lives around this physiological event and to provide support to minimize negative effects.…”
Section: Discussionmentioning
confidence: 96%
“…Although several studies have described the prevalence of menstrual problems among women in South Asia, including in Sri Lanka (Montgomery, 1974;Ferro-Luzzi, 1980;Bang et al, 1989;Bhatia et al, 1997;Bulut, Filippi, & Marshall, 1997;Fillippi et al, 1997;Walraven et al, 2002;Deeb et al, 2003;Kumarapeli, 2006), information on dysfunctions, such as amenorrhea, dysmenorrhea, and menorrhagia, is scarce. The ''culture of silence'' associated with menstruation (Bang et al, 1989;Rani & Bonu, 2003;Schooler et al, 2005;Cooper and Koch, 2007;Johnston-Robledo et al, 2007) and the sensitive and personal nature of the information from women's perspectives, suggested the special value of using qualitative methods to gather information (LeCompte and Schensul, 1999). While the use of these methods and the non-representative sampling methods limited generalizability, this may be balanced against the limitations to survey findings when response rates are poor and reliability uncertain, as one might expect in the study area or elsewhere in South Asia, where menstruation and other bodily functions are considered private and are rarely discussed openly (WHO, 1981;Garg, Sharma, & Sahay, 2001;Walraven et al, 2002).…”
Section: Discussionmentioning
confidence: 99%